2015
DOI: 10.4067/s0717-95022015000100030
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Histometric Evaluations of Pre-Pubertal, Pubertal and Post-Pubertal Vesicular Gland of Indigenous Bulls of Bangladesh

Abstract: SUMMARY:The present observation was aimed to evaluate the gross and histometric parameters of the vesicular glands of indigenous bulls. Twenty-eight bulls of three age groups were selected from the local market: the pre pubertal group A (<1 year n=4), pubertal group B (1.5-2.5 years, n=16) and post pubertal or adult group C (above 3 years, n=8). The weight, length (anterio-posterior), width (latero-medial) and the thickness (dorso-ventral) of the both left and right vesicular glands were recorded separately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 5 publications
(4 reference statements)
2
13
1
Order By: Relevance
“…The results showed that the distributions of glandular acini and ducts were variable throughout the length of the pelvic urethra. Similar to the present findings, glandular tissues were present in the dorsal wall of the cranial portion of the pelvic urethra, whereas the distribution was less than half of the pelvic urethra caudally [10]. On the contrary, the distribution of glandular units in the propria submucosa was more so in the lateral and ventral wall than the dorsal wall of the urethra in buffalo [4].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results showed that the distributions of glandular acini and ducts were variable throughout the length of the pelvic urethra. Similar to the present findings, glandular tissues were present in the dorsal wall of the cranial portion of the pelvic urethra, whereas the distribution was less than half of the pelvic urethra caudally [10]. On the contrary, the distribution of glandular units in the propria submucosa was more so in the lateral and ventral wall than the dorsal wall of the urethra in buffalo [4].…”
Section: Discussionsupporting
confidence: 86%
“…The ducts were lined by pseudostratified columnar epithelium, which transformed into a transitional type towards the urethral opening in rams [12]. However, the epithelial lining of the duct was mostly simple columnar or pseudostratified columnar epithelium in bulls [10]. The disseminate portion of the pelvic urethra was surrounded by a capsule made up of collagenous, elastic, reticular, and smooth muscle fibers, which was ensheathed by the urethralis muscle in buffalo [3,11].…”
Section: Discussionmentioning
confidence: 99%
“…At this status, it has much glandular tissue, thin fibro muscular capsule, and thin interlobar connective tissue, surrounded by a fragile fibro muscular capsule that divides the parenchyma of the gland into numerous lobules. This result disagreed with previous results in indigenous bulls of Bangladesh by Adhikary et al (24). He mentioned that the capsule is composed of collagen and reticular connective tissue fibers.…”
Section: Stimulating Statuscontrasting
confidence: 92%
“…This result was not parallel with the observation in a bull by Hasan and Hamza (14), who mentioned that it has variable size glandular lobules within the loose connective tissue of the urethra. In ram (Ovis aris) and buck (Cyprus hircus), the glandular tissue has welldeveloped alveoli, which lining by simple columnar epithelium and are characterized by the presence of round, oval nuclei (24). This difference may be due to the body of the prostate gland in a dog being well developed compared to the disseminating part, which leads to secretion being more in the body than the disseminating part.…”
Section: Disseminate Portion (Pars Disseminate)mentioning
confidence: 99%
“…This result was not coincided with (17) in boar who recorded that the prostate was lobulated tubule-alveolar type and has only the disseminated part because its glandular tissue distributed through the sub mucosal layer of pelvic urethra, the capsular septa were composed of collagen, reticular fibers and smooth muscles, the serous secretary end pieces and ducts were lined with cuboidal epithelium, while (18) mentioned that the prostate of rabbit was constituted by stroma and glandular acini. On the other hand, (19) in bull reported lobulated with marked the disseminate part. Also in bull the prostate was fibro-muscular gland and composed of tubule-lobulated structure, their alveoli were lined with simple cuboidal epithelium which reacted positively with PAS and alcian blue stains, in tomcat the main excretory ducts of prostate were opening in the pelvic urethra that lined with transional epithelium as well as mentioned by (20).…”
Section: Resultsmentioning
confidence: 95%